The role of unhelpful metacognitive beliefs in psychosis: Relationships with positive symptoms and negative affect. (30th December 2016) - Sellers, Rachel; Gawęda, Łukasz; Wells, Adrian; Morrison, Anthony P.
Abstract: The Self-Regulatory Executive Function ( s -REF) model assumes that a common set of unhelpful metacognitive beliefs have a central role in predisposition to psychological disorder and the maintenance of symptoms and distress. This research aims to test whether the five unhelpful metacognitive beliefs implicated in the model are associated with positive symptoms of psychosis and whether they are a better predictor of negative affect than topological characteristics of positive symptoms. A sample of people with psychosis completed a semi-structured interview about psychotic symptoms and self-report measures of metacognitive beliefs (MCQ-30), anxiety and depression. Hierarchical multiple regression analyses suggested that unhelpful metacognitive beliefs predict negative affect in people with psychosis over and above symptom frequency and other topological characteristics of symptoms captured by the Psychotic Symptoms Rating Scale (PSYRATS). The findings support the application of the metacognitive model to emotional distress in people with psychosis. Highlights: Metacognitive beliefs are associated with psychotic symptoms and distress. Negative metacognitive beliefs are associated with greater negative affect. Metacognitive beliefs predict affect over and above symptom frequency.